Giant cell arteritis causing mesenteric ischemia without cranial manifestations: Report of an unusual case - Pritika Kushwaha; Meeta Singh; Priyanka Bellichuki; Rajdeep Singh (Indian Journal of Pathology and Microbiology)
Giant cell arteritis is a medium to large vessel vasculitis involving most commonly temporal arteries, vertebral and ophthalmic arteries. Giant cell arteritis causing mesenteric ischemia is not so frequent, more so if it occurs without cranial manifestations. Here we present an unusual case of a 26-year-old male patient presenting with subacute intestinal obstruction due to giant cell arteritis leading to mesenteric ischemia.